2022
DOI: 10.3389/fcimb.2022.931696
|View full text |Cite
|
Sign up to set email alerts
|

Combined Transcriptomics and Metabolomics Analyses in Grass Carp Under Anesthetic Stress

Abstract: Ctenopharyngodon Idella, as a common freshwater bony fish, is more susceptible to various diseases than other carp species, so it has been proposed as a test organism for toxicological analysis In this study, C. idella were anesthetized with MS-222 and 2-PE, and the related anesthetic mechanism and toxic effects were revealed by transcriptomics and metabolomics analyses. When the concentration of MS-222 was 80 mg/L and 200 mg/L, 179 and 887 differentially expressed genes (DEGs), respectively, were identified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…To verify the accuracy of the DEGs, qRT-PCR analysis was conducted to compare the consistency in the expression of some genes ( Wang et al., 2022 ). Six differentially expressed genes, namely, ADH-class-P-like (107910431), PER1 (107916248), RbohD (107957571), RAP2-3 (107896651), MT1 (107936947), and XTH9 ((107959252), were randomly chosen ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…To verify the accuracy of the DEGs, qRT-PCR analysis was conducted to compare the consistency in the expression of some genes ( Wang et al., 2022 ). Six differentially expressed genes, namely, ADH-class-P-like (107910431), PER1 (107916248), RbohD (107957571), RAP2-3 (107896651), MT1 (107936947), and XTH9 ((107959252), were randomly chosen ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, combined transcriptomics and metabolomics clarified the toxic effects in grass carp under anesthetic stress. 20 In Sparus aurata, a similar multi-omics approach was applied to evaluate the toxicity of sulisobenzone (BP-4). 21 To fill the aforementioned knowledge gaps, we constructed a chronic exposure model of juvenile crucian carp treated with Del for 28 days and demonstrated that Del treatment led to intestinal dysbiosis and inflammatory symptoms in the crucian carp.…”
Section: Introductionmentioning
confidence: 99%
“…The integrated omics analysis has been adopted by researchers to elucidate the unique pathways and multifaceted mechanisms. For example, combined transcriptomics and metabolomics clarified the toxic effects in grass carp under anesthetic stress 20 . In Sparus aurata , a similar multi‐omics approach was applied to evaluate the toxicity of sulisobenzone (BP‐4) 21 .…”
Section: Introductionmentioning
confidence: 99%